THE EFFECT OF DIRECTED READING THINKING ACTIVITY IN COOPERATIVE LEARNING SETTING TOWARD STUDENTS’ READING COMPREHENSION OF THE ELEVENTH GRADE STUDENTS IN SMA NEGERI 3 SINGARAJA IN ACADEMIC YEAR 2016/2017 - ., Sang Ayu Kompyang Arisetyawati; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk menyelidiki apakah terdapat pengaruh yang berarti terhadap pemahaman membaca siswa kelas sebelas antara siswa yang diajarkan menggunakan Directed Reading Thinking Activity in Cooperative Learning Setting dan siswa yang diajarkan dengan Directed Reading Thinking Activity saja. Penelitian ini adalah penelitian ekperimental dengan Post-Test Only Control Group Design. Penilitian ini dilaksanakan di SMA N 3 Singaraja. Populasi dalam penelitian ini adalah siswa kelas sebelas pada tahun ajaran 2016/2017 dengan sampel dari 65 siswa yang dipilih melalui random sampling. Data dikumpulkan dengan menggunakan test pemahaman membaca. Data yang terkumpul dianalisa menggunakan t-test dibantu dengan SPSS 22.0. Hasil penelitian menunjukan bahwa terdapat perbedaan yang signifikan dalam kemampuan membaca siswa kelas sebelas, dimana siswa yang diajar menggunakan Directed Reading Thinking Activity in Cooperative Learning Setting menunjukkan pemahaman membaca yang lebih baik dibandingkan dengan siswa yang diajar mengunakan Directed Reading Thinking Activity saja (tobs = 4.056, p < 0.05).Kata Kunci : cooperative learning, directed reading thinking activity, kemampuan memahami bacaan This research was aimed at investigating whether there was a significant effect on reading comprehension of the eleventh grade students who were taught by using Directed Reading Thinking Activity in Cooperative Learning Setting and who were taught by using Directed Reading Thinking Activity only. The research was an experimental research with Post-Test Only Control Group Design. The research was conducted at SMA N 3 Singaraja. The population of this research was the eleventh grade students in academic year 2016/2017 with the samples of 65 students who were selected through random sampling technique. The data were collected by using reading comprehension test. The obtained data were analyzed by using t-test assisted with SPSS 22.0. The result of the research showed that there was a significant effect on reading comprehension of the eleventh grade students in which the students who were taught by using Directed Reading Thinking Activity in Cooperative Learning Setting achieved better reading comprehension than who were taught by using Directed Reading Thinking Activity only (tobs = 4.056, p < 0.05).keyword : cooperative learning, directed reading thinking activity, reading comprehension